Feto-maternal Outcomes in Cesarean Section Compared to Vaginal Delivery in Eclamptic Patients in a Tertiary Level Hospital (Journal of Enam Medical College, 2013)
Background: Over  half-a-million women die each year  from pregnancy-related  causes, and  99 percent of these occur in developing countries. In Bangladesh though maternal mortality  rate (MMR) declined  significantly  around 40% in  the  past  decade,  still  eclampsia  accounts  for 20% of maternal deaths. Eclampsia is uniquely a disease of pregnancy, and the only cure  is  delivery  regardless  of  gestational  age.  A  rational  therapy  for  general  management  of  hypertension and convulsion has been established in Bangladesh by the Eclampsia Working  Group.  But  controversy  still  exists  regarding  obstetric  management. Objective: To  evaluate  the  feto-maternal  outcome  in  cesarean  section  compared  to  vaginal  delivery  in  eclamptic  patients. Materials  and  Methods: This  prospective  cohort  study  was  conducted  in  the  department of Obstretics & Gynecology, Dhaka Medical College & Hospital (DMCH), from  January to December 2011. A total 100 eclamptic women with term pregnancy and live foetus  were purposively included in the study (Group I, 50 patients with vaginal delivery and Group  II, 50 with cesarean section). Results: Out  of these 100 patients 56% were aged